Penyelesaian Sengketa Jual Beli Tanah Antara Penjual dan Pembeli (Studi Putusan Mahkamah Agung Nomor 3459/K/Pdt/2020) - Cinta Rizqareka D; Erina Nur Afifa; Rania Syifa Busroni; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Settlement of land sale and purchase disputes between sellers and buyers with a focus on Supreme Court Decision Number 3459/K/Pdt/2020. The dispute arose due to the seller’s breach of contract by refusing to hand over the land object despite the buyer having fully paid the purchase price and completing all procedures for the transfer of rights, including the execution of the PPJB, Power of Attorney, Vacant Possession Deed, and the Sale and Purchase Deed (AJB) before an authorized PPAT. This study aims to analyze the mechanisms for resolving land sale and purchase disputes and to examine the judicial considerations in Supreme Court Decision Number 3459/K/Pdt/2020. The research employs a normative juridical method through an examination of legislation, legal doctrines, and court decisions. The analysis shows that all levels of the judiciary—the District Court, the High Court, and the Supreme Court—found the sale and purchase relationship to be valid and the seller to have committed a breach of contract. The Supreme Court rejected the cassation petition because no error in the application of law was found, while reaffirming the evidentiary strength of authentic deeds and the importance of legal certainty in land transactions. This decision reinforces legal protection for good-faith buyers and provides an important reference for ensuring that land sale and purchase practices proceed in an orderly, lawful manner and prevent future disputes between the parties.